La expresión literaria del trauma histórico en dos novelas contemporáneas latinoamericanas: Amuleto (R. Bolaño, 1999); Insensatez (H. Castellanos Moya, 2004) - López Badano, Cecilia M. T. (Romanica Silesiana, 2023)
Writing about memory involves balancing on the limits of the symbolizable and the unspeakable of trauma – individual and social – putting together puzzles in which some of the pieces do not fit and others have been lost. The aforementioned novels, both within the imaginary of disenchanted impotence in the face of the reconstructive faculty of memory in personalities devastated by state violence, share traits that connect them: both confront the difficulties of a pathological narrative by posing it from a delirious and/or dislocated discursive inquiry in which the authors sustain the literary possibility of anamnesis. The aim of this article is to explore the fragmentary, fetishizing construction of the paradoxes of memory in the aesthetic constitution of both novels as the only possible support in front of the irreparable damage produced by social subjugation. Through stylistic traits, the reconstructive, salvific viability of traumatic memory is renewed, and at the same time put into crisis.